Airflow and heat stress in a metallurgical industrial building under different working conditions. Issue 3 (3rd July 2019) - Zhao, Ruijie; Gosselin, Louis; Tessier, Jayson; Fafard, Mario
ABSTRACT: Potrooms are elongated buildings in which hundreds of aluminum smelting pots are housed, and have the particularity, among others, to be naturally ventilated. A CFD model simulating a potroom is developed to study its thermal comfort when the aluminum smelting pots take in less volume of air so as to facilitate waste heat recovery from the pot draft. The influences of wind and buoyancy on the ventilation performance of the potroom are simultaneously considered. The heat stress during hot weather is estimated for different cases. A 50% reduction in the pot draft rate is assessed in terms of its influence on the heat stress in the potroom. It is found the 50% reduction of pot draft will not cause a significant change in the ventilation pattern of potroom and the draft reduction can be realised without significantly increasing the potroom's heat stress.